Addiction of High Dose of Benzodiazepine: Verona Detox Approach With Flumazenil - Casari, Rebecca; Metastasio, Antonio; Zamboni, Lorenzo; Biasioli, Martino; Campagnari, Simone; Lugoboni, Fabio (Frontiers in Psychiatry, 2022)
Introduction: Since the 1990s there has been evidence of the significant role Flumazenil (FLU) has in benzodiazepines (BZD) detoxes. The Verona Detox approach has been developed for high dose BZD and Z-drug detoxification via contin-uous subcutaneous infusion of FLU, a selective BZD receptor antagonist acting on the BZD subunit of the GABA-A re-ceptor. FLU is licensed in the UK and other countries to treat only BZD overdose although numerous studies have demonstrated its effectiveness in rapidly resetting GABA-A receptors, quickly reducing tolerance and dependence from BZD, and provid-ing a safe and rapid detox from benzodiazepines. Objective: The aim of this article is to provide all healthcare professional who are interested in BZD detoxification with an approach and clear practical information on how to administer FLU. Method: In this article we outline the approach in detail, describing all medical and nursing procedures day by day. This detox treatment is indicated for patients abusing from at least 5 Defined Daily Dose (DDD) of BZDs or Z-drugs. The process lasts 7 days, and is conducted under medical supervision (daily reviews) and continuous nursing (24/7). Dur-ing this period, 7mg of FLU is administered (1mg/24) through an elastomeric pump, via continuous subcutaneous infusion. Conclusion: To this day, the largest database of FLU detoxification was published by our group, showing how this treatment is safe, with very little side effects even in patients with significant medical comorbidities.